Bacillus clausii atenua a mucosite intestinal induzida por 5-fluorouracil em camundongos - Lima, Francisco Ronaldo Farias (2018)
5-Fluorouracil is an antimetabolite commonly prescribed in the treatment of cancer, and its use in highly proliferative tissues brings significant problems such as mucositis. Bacillus clausii (B. clausii) is a bacillary probiotic commonly used in protection against acute diarrhoea and gastrointestinal disorders associated with gastrointestinal dysbiosis. Objectives: To evaluate the effects of probiotic B.clausii on inflammation and gastrointestinal changes in the course of experimental intestinal mucositis induced by 5-FU. Methods: Male Swiss mice (25-30g) were treated with 5-FU (450 mg/kg, i.p.) (5-FU and B. clausii + 5-FU) or saline solution (saline, B. clausii). B. clausii was administered by gavage in volume corresponding to (1×109 CFU) for 3 days after administration of 5-FU, during which time, analysis of weight changes was performed. After 3 days, the animals were sacrificed and samples of duodenum, jejunum and ileum were obtained for evaluation of histomorphometry and histopathology, MPO activity, MDA and GSH levels. Blood samples were taken for the total white blood cell count. In other groups of animals, gastric emptying and intestinal transit, intestinal permeability, intestinal smooth muscle contractility, transepithelial electrical resistance (TEER) and intestinal transport of water and electrolytes were evaluated. The mechanical response was assessed using an isometric force transducer coupled to a data acquisition system. Carbacol (10-10-10-4 M) was applied on smooth muscle of jejunum and ileum. Permeability and TEER were measured in Ussing chambers. Results: Treatment with B. clausii attenuated mucosal injury, reversing the decrease in villus/crypt ratio and body weight. Also, decreased neutrophil infiltration, MDA levels, GSH consumption, gastric retention, water and electrolyte secretion, intestinal hypercontractility, and increased 5-FU-induced intestinal permeability. However, treatment with 5-FU showed increased TEER and B. clausii was not able to decrease these values. Conclusion: The administration of B. clausii may be a new therapeutic approach for intestinal mucositis because this probiotic was able to attenuate 5-FU induced intestinal mucositis in mice.